2009
DOI: 10.3201/eid1503.080711
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsiaspp. in Ticks, Poland

Abstract: Ticks are recognized as the main vectors and reservoirs of spotted fever group rickettsiae. We searched for the most prevalent Rickettsia spp. in Poland and found R. slovaca and R. helvetica bacteria in ticks in southern and central Poland; R. raoulti was found in ticks in all parts of Poland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 15 publications
4
52
1
5
Order By: Relevance
“…The single R. slovaca-positive tick could have fed on a host that was infected with this Rickettsia species. A single I. ricinus tick harboring R. slovaca DNA was found in another epidemiological study (58); nevertheless, the preferential vectors for R. slovaca remain Dermacentor ticks. Growth studies have shown that R. slovaca grown in D. marginatus ticks reaches much higher numbers than it does in I. ricinus ticks.…”
Section: Discussionmentioning
confidence: 99%
“…The single R. slovaca-positive tick could have fed on a host that was infected with this Rickettsia species. A single I. ricinus tick harboring R. slovaca DNA was found in another epidemiological study (58); nevertheless, the preferential vectors for R. slovaca remain Dermacentor ticks. Growth studies have shown that R. slovaca grown in D. marginatus ticks reaches much higher numbers than it does in I. ricinus ticks.…”
Section: Discussionmentioning
confidence: 99%
“…9). These bacteria have been found in Dermacentor marginatus and Dermacentor reticulatus ticks in a great majority of European countries, with a high percentage of ticks infected with these bacteria (208,(280)(281)(282)(283)(284)(285)(286)(287)(288)(289)(290). Dermacentor ticks usually bite hairy domestic and wild animals (291).…”
Section: Tick-borne Rickettsiae In Europe Species Identified As Pathomentioning
confidence: 99%
“…The Borrelia spirochetes have been shown to adhere to human and murine fibroblasts, endothelial cells, epithelial cells, macrophages, neuronal and glial cells, fibrocytes, and lymphocytes (Chmielewski & Tylewska-Wierzbanowska, 2010;Cinco et al, 2001;Coburn et al, 1998;Dorward et al, 1997;Fischer et al, 2003;Grab et al, 1999;Leong et al, 1998;Livengood & Gilmore, 2006;Montgomery et al, 1993;Peters & Benach, 1997;Rupprecht et al, 2006;Sambri et al, 1993;Thomas et al, 1994). Although the Borrelia spirochete is generally referred to as an extracellular pathogen, several investigations performed in vitro with cell cultures have demonstrated the invasive properties of Borrelia bacteria to nonprofessional phagocytic cells (Chmielewski & TylewskaWierzbanowska, 2010;Girschick et al, 1996;Hechemy et al, 1992;Klempner et al, 1993;Livengood & Gilmore, 2006;Ma et al, 1991;Wu et al, 2011).…”
Section: Dissemination and Colonizationmentioning
confidence: 99%